International Trade Dispute Settlement Under Free Trade Agreements: An Analsis of Indonesian Tax Court Verdicts - Prasetia, Tomy; Zulfiqar, Faisal Labib; Baehaqi, Muhammad Nuh; Ilham, Muhammad (BESTUUR, 2025)
This study analyses the lawsuits concerning the ASEAN-Australia-New Zealand Free Trade Area (AANZFTA) trade agreement within the Indonesian tax court between 2018 and 2025. The method of content analysis was performed to systematically categorise 71 verdicts based on the type of dispute, the evidence submitted, and the arguments of both disputants. The results outlined six key areas of disputes: time limits for submission of Certificate of Origin (COO), third party invoices, issuance of electronic COO, tariff classification, typographical errors and issues of completeness of the COO. These findings point to the fact that there exists a clear trend in the grounds for the acceptance and rejection of some decisions. For instance, uncontested cases are typified by data in contrast or different from the customs documents, while contested cases are those where evidence of sound form is submitted in adherence with certain pertinent laws. This trend buttresses the need to clearly and precisely fill in all documents in order to meet all the requirements of preferential tariff treatment as specified under AANZFTA rules. The legal implications of these findings are significant since they underscore that international regulations do not only form the basis of imposing for compliance but ensure that there will be no breeches in the trade relations. Recommendations are made in the research for enhanced management of AANZFTA regulations to prevent further disputes from arising in the future.